Global Research Trends in Green Entrepreneurial Orientation and Environmental Orientation: A Bibliometric Review Based on the Natural Resource-Based View - Suroto Suroto (Politeknik Siber Cerdika Internasional, 2026)
Background: The increasing environmental challenges and sustainability pressures have significantly transformed the way firms formulate their competitive strategies. In response to these global changes, green entrepreneurial orientation and environmental orientation have emerged as critical organizational capabilities that enable businesses to balance economic performance with societal and environmental responsibilities. Despite the growing body of research in this area, existing studies remain fragmented and lack an integrated understanding of the intellectual structure and development trajectory of this research field. Objective: This study aims to map the global research landscape of green entrepreneurial orientation and environmental orientation through a comprehensive bibliometric analysis grounded in the Natural Resource-Based View (NRBV). Methods: Using publications retrieved from the Semantic Scholar database from 2010 to 2025, bibliometric techniques were employed to analyze publication trends, influential authors and journals, collaborative networks, and thematic evolution using VOSviewer software. Results: The findings reveal rapid growth of research interest, with dominant themes focusing on green innovation, sustainable competitive advantage, and business performance. Network, overlay, and density visualizations indicate strong intellectual linkages between entrepreneurial orientation, environmental strategy, and firm-level outcomes, reflecting a recent shift towards innovation-driven sustainability. Conclusion: This study provides an integrated overview of sustainability-oriented strategic orientations and their role in supporting business resilience, offering implications for managers, policymakers, and researchers aligned with sustainable development goals.